Determinants of Consumption Behavior Among the Millennial Generation - Saputra, Aina Aldi; Sarmini, Sarmini; Widiawati, Chyntia Raras Ajeng; Yunita, Ika Romadoni (International Journal of Informatics and Information Systems, 2024)
This study examines the factors influencing consumption behavior among the millennial generation, emphasizing the effects of family size, education level, and income on food, non-food, and total household expenditure. As digitalization and demographic shifts continue to redefine modern lifestyles, understanding millennial consumption patterns offers valuable insights into changing welfare dynamics and economic structures. Employing a quantitative associative approach, data were collected from 120 millennial households through structured questionnaires and interviews, complemented by secondary data from the Central Statistics Agency (BPS). Multiple linear regression analysis was used to evaluate both simultaneous and partial relationships among variables, while descriptive statistics were applied to illustrate the respondents’ socioeconomic characteristics. The findings show that family size, education, and income collectively have a significant influence on consumption across all categories. Partially, family size and income significantly affect food-related spending, whereas education does not exhibit a notable impact in this segment. In contrast, for non-food and total consumption, all three variables display a positive and significant relationship, suggesting that higher income and education levels encourage more diversified expenditures. Moreover, non-food consumption (57.19%) surpasses food consumption (42.81%), supporting Engel’s Law and indicating improved living standards alongside a shift toward lifestyle diversification. Nonetheless, the proportion of non-food expenditure remains moderate, reflecting cautious financial behavior amid lingering post-pandemic income constraints. These findings align with Keynesian and Life-Cycle consumption theories, illustrating how income stability, education, and life-stage factors shape millennial consumption decisions. Overall, this study underscores the evolving nature of millennial households toward technology-driven, experience-based, yet financially mindful consumption patterns, providing implications for policymakers and businesses to enhance income resilience, digital literacy, and sustainable consumption growth in the digital economy.